2012
DOI: 10.1186/1472-6882-12-166
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gut modulatory and bronchodilator activities of Amaranthus spinosus Linn.

Abstract: BackgroundThe aqueous-methanolic extract of Amaranthus spinosus (A. spinosus Linn.,) whole plant, was studied for its laxative, spasmolytic and bronchodilator activities to validate some of its medicinal uses.MethodsThe crude extract of A. spinosus was studied in-vivo for bronchodilator and laxative activities and in-vitro using isolated tissue preparations which were mounted in tissue baths assembly containing physiological salt solutions, maintained at 37°C and aerated with carbogen, to assess the spasmolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…D. laxata has antiinflammatory and antinociceptive activities in vivo 45 . A. spinosus has been shown to have laxative and bronchodilatory effects in vitro 47 . A. spinosus contains rutin 46 , which is widely acknowledged for its nutraceutical effects and several pharmacological effects 48 such as antifatigue 49 , immunostimulatory 50 among others.…”
Section: Discussionmentioning
confidence: 99%
“…D. laxata has antiinflammatory and antinociceptive activities in vivo 45 . A. spinosus has been shown to have laxative and bronchodilatory effects in vitro 47 . A. spinosus contains rutin 46 , which is widely acknowledged for its nutraceutical effects and several pharmacological effects 48 such as antifatigue 49 , immunostimulatory 50 among others.…”
Section: Discussionmentioning
confidence: 99%
“…To assess whether the spasmolytic activity of the test substance was mediated through Ca ++ channel blockade (CCB), the high K + (80 mM), as KCl, was used to depolarize the preparations [19]. The high K + (80 mM) was added to the tissue bath, which produced a sustained contraction.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, involvement of calcium channel blocking activity was observed as underlying cause of spasmolytic effect of crude extract (urRahaman et al, 2013;Chaudhary et al, 2012). To explore possible mechanisms behind spasmolytic effect, high K + (80 mM) and carbachol (1 µM)-induced contraction on isolated rabbit jejunum were challenged with the extract.…”
Section: Discussionmentioning
confidence: 99%
“…All the in vitro experiments were performed as per protocols previously described by (Chaudhary et al, 2012).…”
Section: In Vitro Experimentsmentioning
confidence: 99%